Life’s Tactics and Its Critical Approaches: Reading Nyka-Niliūnas’s Texts - Šmitienė, Giedrė (Colloquia, 2019)
Alfonsas Nyka-Niliūnas’s poetry is hermetic and enriched with cultural images. At the same time, the poet is phenomenologically attentive to experience, and this focus influences his poetics. Nyka-Niliūnas acknowledged that his poetry is a particularly accurate autobiography. Thus, the intent of the article is to “step” into the hermetic world of Nyka - Niliūnas’s poetry by finding the individual base in his works.I employ two methodological approaches by distinguishing existentially open sentences-confessions and observing life’s tactics. The tactics of everyday life, examined in detail by Michel de Certeau, is insignificant and immersed in everyday situations, but with its logic of acting. Using the approach of tactics, on the one hand, a person is only mildly thematized, and on the other, he/she is less exposed to manipulations. This is why for the individual-centered research I have chosen the concept of tactics.In the case of Nyka-Niliūnas, the investigation of tactics leads to the motives of leaving home and allows understanding them not as routine, but as repetitive actions that help to understand situations. The departures arise from a desire to not fully identify with the place where he is and, at the same time, from an openness to another space—be it the surrounding fields, literature, or the Western European culture. The space of endless negotiations and continuous creative tactics opens up between belonging to and differing from one’s own kind.
Keywords: life’s tactics; departure; home; allure of Western Europe; Alfonsas Nyka-Niliūnas